Study of Effective School Factors in High-Risk Behaviors of Adolescents in Qazvin - Ahmad Usefynezhad; Kiumars Farahbaksh; Hossein Salimi Bajestani; Mohammad Asgari (پژوهان, 2022)
Background and Objectives: It is essential to identify factors that can prevent or reduce high-risk behaviors; therefore, the present study aimed to study effective factors related to school in high-risk behaviors of adolescents in Qazvin. Materials and Methods: The research method was qualitative along with conventional content analysis. The statistical population of the study included healthy adolescents exposed to high-risk behaviors and experts (psychologists, counselors and sociologists) in Qazvin in the first six months of 2021. 10 experts were selected by snowball sampling method and 32 adolescents were selected by purposive sampling method. Semi-organized interviews were used to collect data. Theme analysis technique was used to analyze the data. Results: Based on the results of the study of school risk factors in the tendency to adolescents' risky behaviors, sub-themes of school security status, school context, poor support resources at school, school location, inappropriate social atmosphere, inappropriate role models and inappropriate educational programs in school were derived. Conclusions: Based on the lived experience of adolescents and professionals, a set of school related factors are involved with high-risk adolescent behavior. Therefore, the results require more attention of counselors, teachers and officials of institutions related to education in this field.